The iatrogenic thyroid disease treatment - Devaraj, Navin Kumar (University Of Malta, 2022)
Many factors may affect the level of thyroid hormones and thyrotropin. In treating patients, various consideration including the clinical status of the patient and possible confounding factors such as infection and age needs to be considered before starting treatment for either thyrotoxicosis or hypothyroidism. This article will look at the serious iatrogenic effect of thyroxine therapy on an elderly man.